Design of System Batch Injection Analysis (BIA) for Monitoring the Production of Alcohol (II) - Tri Mulyono; Dwi Indarti; Rizqon Rizqon (UNEJ e-Proceeding, 2016)
The main purpose of this work is to report the development of batch injection analysis (BIA) for monitoringvthe production of Alcohol. The activities focus on the concepts BIA and design of syringe pump and stepper pump.vBoth pumps were adjusted flow-rate and controlled by computer with microcontroller Arduino Uno R module usingvsoftware Labview 2013 . The results showed that both pump have a good performance. This was marked by relation coefficient 0,99 and a little variance < 5%.